Inovasi Hukum Pemerintah Kabupaten Tegal dalam Membuat Kebijakan Program Pengentasan Kemiskinan yang Mensejahterakan Masyarakat Berbasis Efisiensi Anggaran - Moh. Taufik; Sugiyanto Sugiyanto; Sanusi Sanusi; Kanti Rahayu (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Poverty is a multidimensional issue that not only involves economic limitations but also reflects violations of fundamental human rights such as the right to food, health, education, decent employment, and socio-political participation. This study aims to analyze the legal innovations implemented by the Tegal Regency Government in formulating poverty alleviation policies based on budget efficiency. Using an empirical and philosophical approach, this research views law not only as an ideal set of norms but also as a dynamic social phenomenon within society. The findings reveal that legal innovation is manifested through the strengthening of juridical aspects in regional policies, the integration and synergy of four flagship poverty alleviation programs, and the implementation of the initiative “One Regional Apparatus, One Assisted Village,” which involves all elements of local government. In addition, active community participation and the utilization of corporate social responsibility (CSR) funds from regional and state-owned enterprises serve as crucial supporting factors in enhancing the sustainability and effectiveness of poverty alleviation programs in Tegal Regency.